Vascular accesses: Which choice? Less is more, more or less - Regina Frontera; Mirko Barone (Open Exploration Publishing Inc., 2023)
In the context of in-hospital care management, the need for infusion therapies involves the choice of appropriate devices. Historically, there is no consensus about the preference for vascular accesses, although the data present in the literature would seem to favor peripheral ones due to fearful complications and a non-negligible rate of bloodstream infections. It is also true the decision for central routes is sometimes dictated by the patient's general clinical conditions (especially as a result of surgery) or by the need to establish continuous short or long-term support therapies. Therefore, it would seem anachronistic to favor one strategy rather than another. Probably data should be reviewed, considering and evaluating the correct application of indications and guidelines for both positioning and management of venous accesses, without facing methodological biases that could lead to scarcy and inconclusive results; although it is undeniable that some conditions promote the onset of complications.